2006
DOI: 10.1002/ejlt.200600032
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the content of free fatty acids in high‐oleic sunflower seeds by near‐infrared spectroscopy

Abstract: Estimating the content of free fatty acids in high-oleic sunflower seeds by near-infrared spectroscopyThe content of free fatty acids (FFA) in vegetable oils represents an important quality factor in oil crops. The objective of the investigation was to develop a near-infrared (NIR) calibration for estimating the FFA content in high-oleic sunflower seeds. A sample set of different varieties from the harvest of 2004 as well as of 2005 from two locations in Germany was used; additionally seeds from 2003 were stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…The presence of high levels of free fatty acids, or free acidity, is due to wet harvest conditions which promote the action of lipases generating these molecules, as well as moist grains during storage (Beratlief and Iliescu, 1997). In sunflower oil FFA varied from 1.19 to 1.35% (w/w) in regular sunflower oil (Kreps et al, 2014), from 0.76 to 1.13% in HOHPSO (Marmesat et al, 2008) and can reach up to 4% in HOSO (Moschner and Biskupek-Korell, 2006). FFA are neutralized during the refining process in order to reduce their undesirable effects as undesirable flavor.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
“…The presence of high levels of free fatty acids, or free acidity, is due to wet harvest conditions which promote the action of lipases generating these molecules, as well as moist grains during storage (Beratlief and Iliescu, 1997). In sunflower oil FFA varied from 1.19 to 1.35% (w/w) in regular sunflower oil (Kreps et al, 2014), from 0.76 to 1.13% in HOHPSO (Marmesat et al, 2008) and can reach up to 4% in HOSO (Moschner and Biskupek-Korell, 2006). FFA are neutralized during the refining process in order to reduce their undesirable effects as undesirable flavor.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
“…[32,45] as well as mineral compositions [38,33,16]. However, most studies concentrate on pure sample sets of wheat [25], maize silage [11,23], herbages, grass silages [30,2], legumes [19,9], rice [48] sunflower [26] or hemp [44]. Reliability of NIRS had been questioned when analysis was performed across different plant species and cultivars [14,39].…”
Section: Focus Of This Studymentioning
confidence: 97%
“…When considering the oxidative stability, the seven oil types differed significantly for mean peroxide value (Table 3).Free fatty acid content is an important oil quality parameter (Moschner and Biskupek-Korell, 2006). The free fatty acid values obtained were below the limit of 2% and indicated that the oil of all seven hybrids was having good oxidative quality.…”
Section: Quality Criteriamentioning
confidence: 99%